Double Yields and Negative Emissions? Resource, Climate and Cost Efficiencies in Biofuels With Carbon Capture, Storage and Utilization - Jafri, Yawer; Ahlström, Johan M.; Furusjö, Erik; Harvey, Simon; Pettersson, Karin; Svensson, Elin; Wetterlund, Elisabeth (Frontiers in Energy Research, 2022)
As fossil-reliant industries turn to sustainable biomass for energy and material supply, the competition for biogenic carbon is expected to intensify. Using process level carbon and energy balance models, this paper shows how the capture of residual CO2 in conjunction with either permanent storage (CCS) or biofuel production (CCU) benefits fourteen largely residue-based biofuel production pathways. With a few noteworthy exceptions, most pathways have low carbon utilization efficiencies (30–40%) without CCS/U. CCS can double these numbers and deliver negative emission biofuels with GHG footprints below −50 g CO2 eq./MJ for several pathways. Compared to CCS with no revenue from CO2 sequestration, CCU can offer the same efficiency gains at roughly two-third the biofuel production cost (e.g., 99 EUR/MWh vs. 162 EUR/MWh) but the GHG reduction relative to fossil fuels is significantly smaller (18 g CO2 eq./MJ vs. −99 g CO2 eq./MJ). From a combined carbon, cost and climate perspective, although commercial pathways deliver the cheapest biofuels, it is the emerging pathways that provide large-scale carbon-efficient GHG reductions. There is thus some tension between alternatives that are societally best and those that are economically most interesting for investors. Biofuel pathways vent CO2 in both concentrated and dilute streams Capturing both provides the best environomic outcomes. Existing pathways that can deliver low-cost GHG reductions but generate relatively small quantities of CO2 are unlikely to be able to finance the transport infrastructure required for transformative bio-CCS deployment. CCS and CCU are accordingly important tools for simultaneously reducing biogenic carbon wastage and GHG emissions, but to unlock their full benefits in a cost-effective manner, emerging biofuel technology based on the gasification and hydrotreatment of forest residues need to be commercially deployed imminently.